Strategic Adaptation and Performance of Private Primary Schools in Kisii Town - Agwata, Cliffe Keoro; Juma, Dennis (Journal of Business and Strategic Management, 2025)
Purpose: The purpose of this research was to establish the influence of strategic adaptation and organizational performance of private primary schools in Kisii town. The specific objectives of the study was to establish the influence of strategic flexibility, strategic innovation, hedging and organizational capabilities on performance of private primary schools in Kisii town. Methodology: The study targeted proprietors from 118 pharmacies in Kisumu. Purposive sampling was used to select the sample for the study. Questionnaires were used in collection of data. Descriptive statistics and multiple regression analysis were used to analyze the data. Findings: From the findings, strategic flexibility, strategic innovation, hedging and organizational capabilities had a significant effect on performance of private primary schools in Kisii town (t = 2.089, p = 0.028; t = 2.630, p = 0.010; t = 2.194, p = 0.022; t = 3.125, p = 0.002 respectively) Unique Contribution to Theory, Policy and Practice: This study enriches Dynamic Capabilities Theory by empirically demonstrating how strategic flexibility, innovation, hedging, and organizational capabilities jointly enhance school performance in a changing educational environment. It informs policy by advocating for structured adaptation strategies within Kenya’s private education sector to improve resilience and competitiveness. For practice, the findings provide actionable insights for school leaders to implement adaptive strategies that align internal capabilities with external demands, thereby improving sustainability and service delivery in private schools.